Peace and citizenship from the chair of peace - García-Noguera, Luis; Vásquez López, Yadira (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The research focuses its interest on determining the impact that the implementation of the Chair of Peace has had in the educational institutions of Ciudad Bolívar in the construction of peace and citizenship. From qualitative research in a hermeneutical perspective and the narrative method, a documentary review was carried out. It is concluded that the approach of the Chair of Peace requires in the school, a holistic perspective that encourages critical reflection on the armed conflict, construction of historical memory, strengthening of the social fabric and fulfillment of the Sustainable Development Goals.